Analysis of Full Face Lifting and Full Face Plasty Techniques in Facial Rejuvenation - Alves, Raphael Moreira (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 40 No 77 (2024): Publicação Contínua, 2024)
This article provides a detailed analysis of facial rejuvenation techniques, Full Face Lifting and Full Face Plastia, exploring their methods, benefits, indications, and clinical considerations. The Full Face Lifting, a minimally invasive technique, uses absorbable and non-absorbable threads to reposition facial tissues, promoting a natural and long-lasting lifting effect, with an emphasis on wrinkle reduction and improved skin elasticity. On the other hand, Full Face Plastia focuses on fat removal and platysma muscle surgery, being particularly effective in cases of pronounced sagging. This article also discusses the importance of a multidisciplinary approach that integrates knowledge of dentistry, plastic surgery, and dermatology, maximizing aesthetic outcomes and ensuring patient safety. The analysis is based on technical reviews, clinical experiences, and ethical considerations, contributing to a comprehensive understanding of these techniques in the context of contemporary facial aesthetics.